2021
DOI: 10.1080/21623945.2021.1970341
|View full text |Cite
|
Sign up to set email alerts
|

A novel immune-related genes signature after bariatric surgery is histologically associated with non-alcoholic fatty liver disease

Abstract: Increasing evidence shows that immune-related genes (IRGs) play an important role in bariatric surgery (BS). We identified differentially expressed immune-related genes (DEIRGs) of adipose tissue after BS by analysing the two expression profiles of GEO (GSE59034 and GSE29409). Subsequently, enrichment analysis, GSEA and PPI networks were examined to identify the hub IRGs and related pathways. The performance of the signature was evaluated by area under the curve (AUC) of the receiver operating characteristic (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“… 32 BMS can reduce the degree of inflammation of adipose tissue and improve the metabolic function of adipose cells, which may be one of the mechanisms for the treatment of obesity and its complications. 33 The regulatory role of gut microbiota in BMS has also been gradually popularized. Haange et al found that after RYGB, the gut microbiota of Actinobacteria, especially Proteobacteria (Pseudomonadota) and Bifidobacteriaceae, was relatively increased, while Firmicutes were decreased.…”
Section: Discussionmentioning
confidence: 99%
“… 32 BMS can reduce the degree of inflammation of adipose tissue and improve the metabolic function of adipose cells, which may be one of the mechanisms for the treatment of obesity and its complications. 33 The regulatory role of gut microbiota in BMS has also been gradually popularized. Haange et al found that after RYGB, the gut microbiota of Actinobacteria, especially Proteobacteria (Pseudomonadota) and Bifidobacteriaceae, was relatively increased, while Firmicutes were decreased.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several changes have been reported to occur in adaptive immunity cells after bariatric surgery, including a reduction in T-cell counts and an increase in B regulatory cells [ 13 ]. The change in immune cell infiltration and differentially expressed immune-related genes in adipose tissue after BS have also been analysed by bioinformatics analysis [ 14 ], and the evidences showed that immune cells may play an important role in the beneficial effects of BS on the treatment of obesity and obesity-related comorbid conditions.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have indicated that NAFLD is linked to metabolic disorders ( Huang and Kong, 2021 ; Luukkonen et al, 2021 ; Osborne et al, 2021 ). Immunity is also involved in the development and progression of NAFLD ( Barrow et al, 2021 ; Huby and Gautier, 2021 ; Song et al, 2021 ). Nonetheless, there is still a lack of insensitive and targeted biomarkers that may be widely used in the clinical setting, which causes significant challenges for clinical diagnosis and treatment, especially for early diagnosis and follow-up strategy.…”
Section: Introductionmentioning
confidence: 99%